A Wearable Electrowetting on Dielectrics Sensor for Real‐Time Human Sweat Monitor by Triboelectric Field Regulation. (12th June 2022) - Shen, Hao; Lei, Hao; Gu, Mingwei; Miao, Sheng; Gao, Zhenqiu; Sun, Xuhui; Sun, Lining; Chen, Guanyu; Huang, Haibo; Chen, Liguo; Wen, Zhen
Abstract: Wearable sweat sensors can analyze the abundant composition of solutes and metabolites in sweat to reflect the health state of the wearers in real time. The realization of active motion control for sweat droplets is significant for a multifunctional sweat monitoring device with several analysis chambers. Here, a wearable droplet‐based human sweat monitoring platform (WSMP), by combining an electrowetting on dielectrics (EWOD) device and a triboelectric nanogenerator (TENG), is demonstrated. It allows to collect and transport sweat droplets in different chambers by dielectric wetting effect and eventually merge and react with a pH indicator. The mechanical and electrical model of WSMP is introduced to describe the relationship between the open‐circuit voltage of the TENG and the voltage applied on the EWOD device. The high‐voltage electrical field generated by the TENG can change the wettability of solid–liquid interfaces and realize the controlling of droplet motion. The contact angle of electrolyte droplets changes over 30% with the triboelectric voltage of 5 kV. The driving, merging, and color reaction can be realized by actively controlling the motion of droplets. Finally, a wearable WSMP worn on the shank successfully demonstrates the preliminary detection of the pH level of human sweat. Abstract : A wearable droplet‐based human sweat monitoring platform achieved by combining an electrowetting on a dielectrics device and a triboelectric nanogenerator is demonstrated. The sweat droplets are actuated by dielectric wetting effect to realize the microreaction with indicator, and the pH level of sweat can be also detected. This work will promote the progress toward the practical application of wearable sweat sensors.